Jumpstart CMM/CMMI software process improvements Using IEEE software engineering standards - Land, Susan K. (Practitioners, 2006)
A brilliant instruction set for achieving CMM(a) and CMMI(a) Level 2 requirementsMany organizations, in their push to complete a successful Level 2 CMM or CMMI appraisal, make sizable investments to develop and document their software processes. This book helps these organizations save both time and money while skillfully moving from the chaos of a free-form software development process to one that is controlled, documented, and repeatable. Specifically, the author demonstrates how the application of select IEEE Software Engineering Standards ensures the production of higher quality, reproducible software products.Although the CMM and CMMI set forth standards in six Key Process Areas (KPAs) that must be satisfied to achieve Level 2 accreditation, they do not provide guidance on how to reach these standards.